Francisella tularensis, Tularemia and Serological Diagnosis - Maurin, Max (Frontiers in Cellular and Infection Microbiology, 2020)
Tularemia is a zoonotic disease caused by the bacterium Francisella tularensis. The predominant sources, routes of infection, and clinical manifestations of human infections greatly vary according to the geographic area considered. Moreover, clinical suspicion of tularemia is often tricky because of the lack of specificity of the clinical manifestations. Because F. tularensis isolation is tedious and detection of its DNA usually requires removal of infected tissues, serological techniques are most often used for diagnostic confirmation. However, these techniques are varied and poorly standardized. The microagglutination test (MAT), the indirect immunofluorescence assay (IFA), and ELISA tests are currently the most frequently used techniques. These home-made and commercial tests are mainly used for tularemia diagnosis but also seroprevalence studies. ELISA tests detect specific antibodies within two weeks of disease evaluation, compared to 2–3 weeks for MAT and IFA. However, more false-positive results are usually reported with ELISA. The long-term persistence of anti-F. tularensis antibodies in patients with past tularemia infection hampers the diagnostic specificity of all these tests. Also, cross-reacting antibodies have been described (especially with Brucella and Yersinia species), although usually at a low level. The immunoblotting technique can highlight these serological cross-reactions. Tularemia remains an underdiagnosed disease in most endemic areas, and the clinical presentations of this disease are evolving. It is necessary to improve further speed and accuracy of tularemia diagnosis, as well as the standardization of diagnostic procedures.